2018
DOI: 10.1097/bto.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Combined Anterior Cruciate Ligament and Anterolateral Ligament Reconstruction

Abstract: Background:Graft rupture rate, return to sport and persistent rotational instability remain a concern postoperatively following anterior cruciate ligament (ACL) reconstruction. The anterolateral ligament (ALL) has recently been shown to act as a lateral knee stabilizer that helps improve rotational stability. To improve functional and clinical outcomes, a combined ACL reconstruction with an associated ALL reconstruction has been proposed.Purpose:The main purpose of this study was to evaluate the clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…However, five of the patients in the combined ALL and ACL reconstruction group in their study had a pivot shift of grade 1 or 2, and four had an IKDC score of C at the final follow-up. On the other hand, none of the patients in the ALL STA group in our study had a pivot shift of grade 1 or 2 at the final follow-up, and none had an IKDC score of C. Delaloye et al [27] demonstrated that compared with ACL reconstruction only, combined ACL and ALL reconstruction in a high-risk population is associated with significantly decreased graft rupture rates. Marcacci et al [28] reported a graft rupture rate of 2%.…”
Section: Table III Comparison Of Postoperative Outcomes Among Groupscontrasting
confidence: 50%
See 1 more Smart Citation
“…However, five of the patients in the combined ALL and ACL reconstruction group in their study had a pivot shift of grade 1 or 2, and four had an IKDC score of C at the final follow-up. On the other hand, none of the patients in the ALL STA group in our study had a pivot shift of grade 1 or 2 at the final follow-up, and none had an IKDC score of C. Delaloye et al [27] demonstrated that compared with ACL reconstruction only, combined ACL and ALL reconstruction in a high-risk population is associated with significantly decreased graft rupture rates. Marcacci et al [28] reported a graft rupture rate of 2%.…”
Section: Table III Comparison Of Postoperative Outcomes Among Groupscontrasting
confidence: 50%
“…Delaloye et al[ 27 ] demonstrated that compared with ACL reconstruction only, combined ACL and ALL reconstruction in a high-risk population is associated with significantly decreased graft rupture rates. Marcacci et al[ 28 ] reported a graft rupture rate of 2%.…”
Section: Discussionmentioning
confidence: 99%
“…62 proposed chronic ACL lesion, the presence of a grade 3 pivot shift, participation in high level sports, an associated Segond fracture or a lateral femoral notch sign on conventional radiographs as indications for combined ACL and ALL reconstruction. In technical notes, the use of iliotibial tract 63 and gracilis autografts 64 as well as arthroscopic ALL identification 65 have been described. Sonnery-Cottet and colleagues 20 re-evaluated the subjective outcomes following combined ACL and ALL reconstruction in 83 patients and reported no specific complications in their sample after a minimum follow-up of two years.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of an ALL reconstruction demonstrated a very low complication rate (0.5%) related to the ALL graft. 49 Some specific complications of ALL reconstruction were observed in included studies, such as pretibial…”
Section: Discussionmentioning
confidence: 99%